Social Security Distortions onto the Labor Market : Estimates for Colombia - Cuesta, Jose; Olivera, Mauricio (2012)
This paper identifies and quantifies three distortions caused by the existing social security and social assistance systems in Colombia. These distortions refer to the discrepancy between the cost of formal social security for the employer and the worker's valuation of the received service (social distortion): the differences in social security benefits received by salaried and self-employed formal workers (occupational distortion); and the discrepancy caused by the cost in employing a formal instead of an informal worker (informal distortion). Based on recently collected information concerning Colombian workers' willingness to pay for several packages of social security benefits, the study calculates that social distortions range from 2 to 27 percent of the workers' labor earnings; the occupational distortion amounts to 50 percent of formal salaried workers' earnings; and the informal distortions represent between 45 and 56 percent of formal workers' labor income. Results indicate that valuations of the contributive and noncontributive protection systems play a key role in explaining these distortions. In addition, the Colombian social protection system thereby places a hefty tax on the formal worker (and employer) while transferring resources to the informal worker, but these distortions are not sufficient to revert differentials in earnings among formal and informal workers.